Social health of people with dementia during the SARS-CoV-2 pandemic. (October 2021) - Lenart, Marta; Mackowiak, Maria; Senczyszyn, Adrianna; Szczesniak, Dorota; Giebel, Clarissa; Chattat, Rabih; Gabbay, Mark; Lion, Katarzyna; Moyle, Wendy; Ottoboni, Giovanni; Rymaszewska, Joanna; Tetlow, Hilary; et al.
Abstract : Background: Limited access to medical and social services during the coronavirus outbreak has contributed to the exclusion of vulnerable populations, such as people with dementia and older adults. These limitations and the resulting social isolation have highlighted the importance of social relationships and their relationship to the mental health of these people. In the context of dementia, 'social health' (SH) can be defined as the role of social abilities for achieving a dynamic balance between opportunities and limitations. The concept encompasses the capacity and independency of an individual to participate in social activities alongside the influences of the surrounding social network. Methods: Using a qualitative and quantitative approach, we will present social health and its determinants of people with dementia related to social care service closures and self-isolation during the SARS-CoV-2 pandemic. We present an analysis of the survey data from the cross-country population- based study and the semi-structured telephone interviews with people with and without dementia from Poland, UK, Australia and Italy aged 65 and over. Results: Measuring the Social Health Index in relation to experiencing self-isolation and changes in the use of services before and during the pandemic among the people with dementia, allow us to identify the level of SH and its determinants. Also, the qualitative results revealed the indirect consequences of the pandemic-related restrictions in the access to social care service and social isolation. Reduction of social support was significantly related to deficits in social health and well-being. Conclusions: Our results highlight the emerging impact of health the current global epidemiological situation upon social health, with a particular focus on those affected by social disadvantage and isolation.